The present situation and the future perspectives of foreign direct investment in Balkan Region - Arjan Qefalia; Pleurat Rexhepi (Contemporary Economics, 2009)
The past decade has witnessed increased globalization of the world economy as result of technological changes, trade liberalization and privatization policies. Balkan countries as developing nations are in the realization process of the globalization changes of the world economy. Being in the process for entry into the EU, many changes are being done to integrate with the global economic trends. The research has shown that after the fall of communism in the 1990s the Balkan Region brought significant political and economic changes. The change in attitude led to a removal of direct blockage for FDI. As a result, continued deregulation and privatization has been widespread. However, history of FDI is relatively short for Balkan Region in comparison with other countries. The economy opened up capital inflows only at the beginning of 1990s, and is still showing low shares in the total of Central and Eastern European flow. Despite Balkan's competitive advantage due to its geographical location and its resources, it is still far from other Central European countries in achieving the same level of FDI. This situation came as a result of: political instability, low intraregional trade, the small size of national markets, huge institutional corruption and weak judiciary system. Among the more successful Balkan recipients of FDI has been Bulgaria and Romania, while Greece has been a major source of FDI for the transition economies of the Balkan region. Greek investment is driven in part by the availability of low cost labor in the nearby transition economies. The focus of this article is to analyze and evaluate the current performance of FDI in Balkan Region and how the governments can improve this performance.
Keywords: 330